Professional iPhone and iPad database application programming - Alessi, Patrick (New Delhi : wiley publishing, Inc Chichester : John Wiley [distributor], 2011)
"An enormous demand exists for getting iPhone applications into the enterprise and this book guides you through all the necessary steps for integrating an iPhone app within an existing enterprise. Experienced iPhone developers will learn how to take advantage of the built-in capabilities of the iPhone to confidently implement a data-driven application for the iPhone."--Publisher's description.
PART I: MANIPULATING AND DISPLAYING DATA ON THE IPHONE AND IPAD -- Introducing data-driven applications -- The iPhone and iPad database: SQlite -- Displaying your data: the UITableView -- IPad interface elements -- PART II: MANAGING YOUR DATA WITH CORE DATA -- Introducing Core Data -- Modeling data in Xcode -- Building a Core Data application -- Core Data-related Cocoa features -- Core Data migration and performance -- PART III: APPLICATION INTEGRATION USING WEB SERVICES -- Working with XML on the iPhone -- Integrating with web services -- Appendix A: Tools for troubleshooting your applications.
All age.
Keywords: iPhone (Smartphone) -- Programming; iPad (Computer) -- Programming; Application software -- Development